MicroRNAs and lung cancer: overview of essential pathways and somatic mutations in cancer progression - Tirpe, Andrei-Alexandru; Nutu, Andreea; Busuioc, Constantin; Pop, Ovidiu-Laurean; Berindan-Neagoe, Ioana (Frontiers in Oncology, 2025)
Lung cancer is the most frequently diagnosed type of cancer worldwide, according to GLOBOCAN 2022 statistics. Key genetic alterations involve driver gene mutations that significantly enhance cancer aggressiveness. These include several EGFR mutations, ALK rearrangements, ROS1 rearrangements, RET translocations, MET alterations, NTRK fusions, BRAF mutations and KRAS mutations, such as the KRAS G12C mutation. Naturally, each of these is part of a larger signaling pathway that becomes dysregulated via genetic alterations. We highlight the transduction of EGFR: HER2 via RAS-RAF-MEK-MAPK pathway, PI3K-PTEN-AKT pathway and STAT pathway, of the ALK via PI3K/AKT, MAPK/ERK and JAK/STAT and of KRAS via effectors of the MAPK pathway and of the PI3K pathway. MicroRNAs (miRNAs) interfere at various levels with these pathways, either with pro-oncogenic effects or tumor suppressive effects. For instance, miR-33a is a tumor suppressive miRNA with a role in EGFR-tyrosine kinase inhibitor (TKI) resistance, miR-200c regulates the ALK pathway, and miR-22-3p regulates the MET pathway. The present paper also serves as an integrative work, highlighting the main cancer progression processes regulated by miRNAs, following these mutations. Specifically, we highlight the modulatory roles of miRNA in cancer cell survival and proliferation (miR-28, miR-30b/c), invasion and metastasis (miR-218, miR-182), neoangiogenesis (miR-29c), metabolic reprogramming (miR-124), and therapy resistance (miR-378, miR-328, miR-1244). The broad implications of miRNAs in lung cancer underline their potential real-world utility, as these entities can function as biomarkers for prognosis/diagnosis and even future therapeutic targets or agents.